Effect of ceramic material type on the fracture load of inlay-retained and full-coverage fixed dental prostheses - Hamid Kermanshah; Fariba Motevasselian; Saeedeh Alavi Kakhaki; Mutlu Özcan (Medical Journals Sweden, 2020)
Objective Ceramic inlay-retained fixed partial denture (IRFPD) is a conservative prosthetic option but the mechanical durability of new high strength zirconia reinforced glass ceramic FPDs is not investigated. The purpose of this study was to compare fracture load of 3-unit ceramic FPDs. Materials and methods Extracted premolars and molars (N = 64) were used to create three test groups (IRFPDs) and one control group (full coverage FPD) (n = 8). The teeth were embedded in PMMA resin with a mesiodistal distance of 6 mm. Premolars had a distal and molars had a mesial inlay preparation (width: 3 mm; height: 4 mm) in the test groups. IRFPDs were made from a zirconia reinforced lithium silicate (VS) or a monolithic zirconia. Zirconia IRFPDs received 2 types of surface treatments: sandblasting (Zr-IRFPD) or internal coating with feldspathic porcelain (ZrC-IRFPD). Control group was made from monolithic zirconia with the same connector size and zirconia surfaces were sandblasted (Zr-FPD). All restorations were cemented using a resin luting cement. After 5000 thermo-cycles, fracture load values (N) were determined with a universal testing machine at a crosshead speed of 0.75 mm/min. Data were analyzed using 1-way ANOVA and Tukey`s post hoc test (p ˂ .05). Result Fracture load (mean ± SD) of Zr-FPDs, Zr-IRFPDs and ZrC-IRFPDs were 672 ± 183, 672 ± 123 and 638 ± 59, respectively, being not statistically different (p > .05). VS-IRFPD exhibited statically lower values (391 ± 136). The predominant mode of failure was fracture at the connector area in all groups. Conclusion The fracture load of 3-unit IRFPD was significantly affected by types of ceramics but the retainer design and surface treatment in Zr groups did not show a significant effect.